Kolegium Filmowe 2014–2015: TVP w służbie kinematografii - Majer, Artur (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article discusses the functioning of the Film Council during its activity in Telewizja Polska in 2014–2015. In less than two years the Council consisting of over a dozen members from several TVP’s departments recommended almost forty coproductions for feature films, regulated procedures for the endorsement of coproduction agreements and aimed to develop TVP’s influence in the process of film promotion and distribution. According to Polish film law, the Council’s job was to stimulate the development of the Polish cinema.